The effects of physical exercise with additional visual tasks on vision and anxiety in children aged 10–11 years - Zhu, Guiming; Wang, Miyu; Wang, Jingchi; Li, Pengfei; Jiang, Limei; Shi, Haijie; Yin, Rongbin; Ding, Junjie (Frontiers in Psychology, 2025)
PurposeThis study investigated the effects of physical exercise with additional visual tasks on anxiety and visual acuity in children aged 10–11 years, and analyzed the mediating role of visual acuity in this relationship.MethodsFifth-grade students from an experimental elementary school in Suzhou were selected and randomly assigned into a control group (n = 81) and an experimental group (n = 80). The experimental group underwent 16 weeks of physical exercise with additional visual tasks, while the control group engaged in regular physical exercise. Uncorrected distance visual acuity (UDVA), kinetic visual acuity (KVA), and anxiety levels were measured both before and after the experiment.ResultsPost-intervention, the experimental group showed significant improvements in left and right eyes UDVA and KVA (P < 0.01) and a significant reduction in total anxiety scores (P < 0.01). The control group exhibited significant improvements in left and right eyes UDVA (P < 0.05), but not in KVA (P > 0.05), with a significant reduction in anxiety scores (P < 0.01). Significant positive correlations were found between left and right eyes UDVA and KVA, and significant negative correlations between total anxiety scores and both left and right eyes UDVA and KVA. In the experimental group, KVA and left eye UDVA mediated the impact of physical exercise with additional visual tasks on anxiety.ConclusionPhysical exercise with additional visual tasks improved UDVA and KVA in children aged 10–11 and effectively reduced anxiety in fifth-grade students. KVA and left eye UDVA acted as chain mediators in this effect.